2010
DOI: 10.1136/gut.2009.209023b
|View full text |Cite
|
Sign up to set email alerts
|

PTH-015 Specialist gastroenterology involvement inStreptococcus bovispositive cultures

Abstract: IntroductionThere is well documented evidence linking Streptococcus bovis (S bovis) bacteraemia to colonic neoplasms and polyps. As patients with S bovis bacteraemia can be found across various specialities, our aim was to audit the consistency of appropriate specialist referral for assessment of colonic pathology.MethodsAll cases of S bovis bacteraemia occurring between October 2000 and June 2009 were identified using information provided by the department of microbiology. Medical records were reviewed for cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…The percentage of patients undergoing colonoscopy varies widely in reports from other centers (38-100%) [9,[11][12][13][14][15][16]; however it is not always clear whether they excluded patients who died during the index hospitalization, were made palliative, or had known CRC. One study auditing the consistency of specialist referral found that 10/13 (77%) cases were referred to gastroenterology after excluding seven patients judged to have a prognosis so poor as to preclude further investigations [17]. We found that a similar percentage of patients were referred for colonoscopy in our study.…”
Section: Discussionsupporting
confidence: 65%
“…The percentage of patients undergoing colonoscopy varies widely in reports from other centers (38-100%) [9,[11][12][13][14][15][16]; however it is not always clear whether they excluded patients who died during the index hospitalization, were made palliative, or had known CRC. One study auditing the consistency of specialist referral found that 10/13 (77%) cases were referred to gastroenterology after excluding seven patients judged to have a prognosis so poor as to preclude further investigations [17]. We found that a similar percentage of patients were referred for colonoscopy in our study.…”
Section: Discussionsupporting
confidence: 65%